2013
DOI: 10.1093/eurheartj/eht368
|View full text |Cite
|
Sign up to set email alerts
|

Persisting gender differences and attenuating age differences in cardiovascular drug use for prevention and treatment of coronary heart disease, 1998–2010

Abstract: Age differences in drug use tended to attenuate over time, whereas gender differences persisted. Areas potentially for improvement are in the hospital treatment of ACS in young women, in secondary prevention among young women and the elderly, and in the continuity of drug use in secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 28 publications
9
56
1
1
Order By: Relevance
“…For example, the age, sex, ethnic and racial characteristics of cardiovascular patients have been widely reported in clinical research. 1,3739 Numerous studies have also demonstrated that married adults have significantly lower rates of CVD and generally live longer with the disease than those who are not married. 4042 In terms of socioeconomic background, studies have shown that adults with higher levels of socioeconomic status (i.e., more education and income) have lower rates of cardiovascular illness and better health outcomes than adults with lower levels of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the age, sex, ethnic and racial characteristics of cardiovascular patients have been widely reported in clinical research. 1,3739 Numerous studies have also demonstrated that married adults have significantly lower rates of CVD and generally live longer with the disease than those who are not married. 4042 In terms of socioeconomic background, studies have shown that adults with higher levels of socioeconomic status (i.e., more education and income) have lower rates of cardiovascular illness and better health outcomes than adults with lower levels of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2012 AHA national survey of American women, younger women were less aware that cardiovascular disease was the leading cause of death in women and were less likely to engage in activities that reduce cardiovascular risk [34]. Koopman et al, showed that women less than 55 years of age were less likely to be prescribed a lipid lowering agent for primary prevention [35]. Hawkins et al demonstrated that the rate of prescriptions for secondary prevention in stable angina was 10% lower in younger women than men [36].…”
Section: Discussionmentioning
confidence: 99%
“…Information on drug use came from the PHARMO Database Network, linking pharmacy and hospitalization records of over 2.3 million subjects. [22–24] Data on drug use in the community came from the general practitioners (GP) register HNU (Huisartsen Netwerk Utrecht). Data of major cardiovascular risk factors (blood pressure, cholesterol, body mass index (BMI), diabetes, smoking, physical inactivity) came from the Doetinchem/MORGEN (RIVM) cohort for those aged up to 65 years and the LASA (Longitudinal Aging Study Amsterdam) cohort for those aged 65 years and over.…”
Section: Methodsmentioning
confidence: 99%